Multistage magma emplacement and progressive strain accumulation in the shallow‐level Krkonoše‐Jizera plutonic complex, Bohemian Massif. Issue 5 (17th October 2013) - Žák, Jiří; Verner, Kryštof; Sláma, Jiří; Kachlík, Václav; Chlupáčová, Marta
Abstract [1] Field relationships combined with new U‐Pb zircon geochronology suggest that the shallow‐level Krkonoše‐Jizera plutonic complex, northern Bohemian Massif, was assembled successively from bottom to top, starting with emplacement of the separately evolved S‐type Tanvald granite (317.3 ± 2.1 Ma), followed by at least two voluminous batches of the I‐type porphyritic Liberec (319.5 ± 2.3 Ma) and Jizera (320.1 ± 3.0 Ma and 319.3 ± 3.7 Ma) granites. The intrusive sequence was completed by uppermost, minor intrusions of the equigranular Harrachov (315.0 ± 2.7 Ma) and Krkonoše granites. The I‐type granites exhibit an unusually complex pattern of superposed feldspar phenocryst and magnetic fabrics as revealed from the anisotropy of magnetic susceptibility (AMS). The outer Liberec granite preserves margin‐parallel foliations and lineations, interpreted to record emplacement‐related strain captured by cooling from the pluton floor and walls. In contrast, the inner Jizera, Harrachov, and Krkonoše granites were overprinted by synmagmatic strain resulting from dextral movements along regional strike‐slip faults cutting the opposite ends of the plutonic complex. Late‐stage felsic dikes in the Liberec and Jizera granites reorient from horizontal to vertical (lineation‐perpendicular) attitude in response to changing the least principal stress direction, whereas mafic schlieren do not do so, representing only randomly oriented small‐scale thermal‐mechanical instabilities in the phenocryst framework. In general, this case example challenges the common approach of inferring pluton‐wide magma flow from interpolated foliation, lineation, and schlieren patterns. More likely, magmatic fabrics in large plutons record complex temporal succession of superposed strains resulting from diverse processes at multiple scales.